Socio-cultural dimensions, employee-related assumptions and HRM practices-a multivariate model in a cross-national setting - Papadionysiou Evangelia; Myloni Barbara (Cogent Business & Management)
The purpose of this study is to present in what way socio-cultural dimensions and employee-related assumptions are related to human resource management (HRM) practices in different areas, as Scandinavia and Greece. These locations were selected as they belong to two distinct cultural clusters, thus making cultural differences more apparent. Interestingly, not much research has compared these specific countries, making it worthwhile to explore the differences or similarities that may exist. Specifically, different environmental forces such as national and organizational cultures are analyzed in depth in order to provide comprehensive insights on their impact on human resource management practices in these different countries. Influenced by the theoretical model of Aycan and Kanungo, we develop and test hypotheses that indicate how several socio-cultural dimensions and employee-related assumptions relate to human resource management practices. SPSS was used to test our hypotheses. Some of our preliminary results reveal that characteristics of national culture such as paternalism, power distance, fatalism, loyalty towards community are linked with organizational culture characteristics, such as participation, responsibility seeking, proactivity and obligation to others. Awareness of these links could enable firms to create or improve some HRM practices based on these elements and give motives to enhance employees’ performance.